Розробка компонентів інформаційної системи для платформи обміну навичками з рекомендаційною функцією підбору партнерів для навчання - Бондаренко, Д. В.; Колесник, О. Б. (ХНУРЕ, 2025)
The report examines the development of an information system for a skill-sharing platform that facilІТates personalized partner matching for learning. The system enables users to register, create profiles, and specify skills they wish to learn or teach. A recommendation algorІТhm analyzes user data to suggest optimal learning partners. The platform also includes administrative functions for managing the catalog of skills and reviewing user-submІТted skill proposals. The implementation of this system aims to enhance the efficiency of skill exchange by automating partner selection and simplifying the process of finding suІТable learning companions.
Keywords: skill-sharing platform; підбір партнерів для навчання